Reactive oxygen intermediates target CC(A/T)6GG sequences to mediate activation of the early growth response 1 transcription factor gene by ionizing radiation. - Datta, R (1993)
The cellular response to ionizing radiation includes induction of the early growth response 1 gene (EGR1). The present work has examined the involvement of reactive oxygen intermediates (ROIs) in this response. Exposure of human HL-525 cells, an HL-60 subclone deficient in protein kinase C-mediated signaling, to both ionizing radiation and H2O2 was associated with increases in EGR-1 transcripts. These increases in EGR-1 expression were inhibited by the antioxidant N-acetyl-L-cysteine (NAC). Nuclear run-on assays demonstrate that NAC inhibits the activation of EGR1 transcription by these agents. Previous studies have shown that induction of EGR1 by x-rays is conferred by serum response or CC(A/T)6GG (CArG) elements. The present studies demonstrate similar findings with H2O2 and the finding that activation of the EGR1 promoter region containing CArG elements is abrogated by NAC. Moreover, we show that NAC inhibits the ability of a single CArG box to confer x-ray and H2O2 inducibility when linked to a heterologous promoter. Taken together, these findings indicate that ROIs induce EGR1 transcription by activation of CArG elements.